Public Policy and Strategic Communication in Addressing Violence Against Women and Children in Public and Digital Spaces: A Conceptual Review for National Resilience in Indonesia - May May Maysarah; M. Adnan Madjid; Mitro Prihantoro; L.Y Wawan Rukmono; Reyhan Fakhreja (International Journal of Computer Information Systems and Industrial Management Applications, 2026)
Violence against women and children in public and digital spaces has become a complex issue that threatens individual safety and undermines social stability and national resilience. Existing studies rarely examine this issuses from the perspectives of public policy, strategic communication, and non-traditional security. This research investigates violence against women and children as a communicative and discursive phenomenon with direct consequences for national resilience and human security. Using a qualitative literature review approach, this study systematically examines academic publications, policy documents, and legal frameworks related to gender-based violence, digital communication, and national resilience, drawing on peer-reviewed publications and official government reports from 2014 to 2024. A descriptive-analytical framework was applied to identify thematic patterns and policy responses to persistent violence against women and children in Indonesia. The results show that Indonesia has established legal frameworks such as Law No. 12 of 2022 on Sexual Violence and Law No. 35 of 2014 on Child Protection, yet enforcement remains weak due to insufficient inter-agency coordination and limited gender awareness among law enforcement officials. From a strategic communication perspective, this fragmentation reflects weak public communication governance, resulting in ineffective policy delivery and public awareness. This study argues that gender-based violence should be understood not only as a social and legal issue but also as a strategic communication challenge affecting social cohesion and national security, underscoring the need for stronger cross-sectoral policy integration and inclusive communication strategies.